Flipbook Ekspansi Kofaktor Terkait Kemampuan Berpikir Kreatif - Deti Ahmatika; Yayu Laila Sulastri; Tami Rizkya Amalia (SJME (Supremum Journal of Mathematics Education), 2022)
The purpose of this study was to determine the validity of the learning design and the validity flipbook of the cofactor expansionwith the plomp model related to creative thinking skills, and to determine the implementation of the cofactor expansion learning design with the Plomp model related to creative thinking skills assisted by theapplication flipbook. The method used in this research is design based research according to Plomp. Sources of data in this study are learning design validators, applications, and small groups. The instruments used in this study were design and application validation sheets, creative thinking skills tests and student response questionnaires. In this research, which is developed is learning design with the help ofapplication flipbook. The data obtained were analyzed using percentages which were interpreted according to their qualifications. Based on the results of the analysis, it can be concluded that the learning design developed is very valid, the flipbook developed is very valid, the implementation is related to creative thinking skills in the complete category, and student responses meet positive criteria. It is recommended that further research be carried out for large-scale implementation, or other mathematical abilities.